The new effector AbSCP1 of foliar nematode (Aphelenchoides besseyi) is required for parasitism rice - Xin HUANG; Yuan-kai CHI; Addisie Abate BIRHAN; Wei ZHAO; Ren-de QI; De-liang PENG (Journal of Integrative Agriculture, 2022)
Plant parasitic nematodes secrete effector proteins to parasitize hosts successfully. Of these proteins, serine carboxypeptidases have critical roles in pathogenicity. This study investigated the role of new effector AbSCP1 in Aphelenchoides besseyi pathogenicity. In situ hybridization and qRT-PCR analyses indicated that AbSCP1 was exclusively expressed in the esophageal glands and upregulated in juveniles. Subcellular localization assays indicated that the protein was expressed in the nucleus. The ability to hydrolyze C-terminal amino acid residues was proven for AbSCP1. Moreover, RNAi significantly reduced the expression of AbSCP1 and RNAi-treated nematodes’ reproductive potential. Pathogenicity assays on rice showed that RNAi-treated nematodes were less pathogenic than the untreated control groups. These results suggest the important role of AbSCP1 in the A. besseyi infection process.